The Impact of Living with Klinefelter Syndrome: A Qualitative Exploration of Adolescents and Adults. Issue 4 (10th November 2016) - Turriff, Amy; Macnamara, Ellen; Levy, Howard P.; Biesecker, Barbara
Abstract: Klinefelter syndrome (XXY) is a common yet significantly underdiagnosed condition with considerable medical, psychological and social implications. Many health care providers lack familiarity with XXY, resulting in medical management challenges and a limited understanding of the personal impact of the condition. Genetic counselors benefit from understanding the challenges adolescents and men with XXY face to effectively address their medical and psychosocial needs. The purpose of this study was to understand the impact of living with XXY as an adolescent or an adult. Individuals aged 14 to 75 years with self‐reported XXY were recruited from online support networks to complete a web‐based survey that included open‐ended questions. Open‐ended responses were coded and analyzed thematically ( n = 169 to 210 for each open‐ended question). Over half of respondents to the open‐ended questions reported challenges in finding health care providers who are knowledgeable about XXY, with many describing an extensive diagnostic odyssey and relief when receiving a diagnosis. Individuals sought support coping with the challenges they face and acknowledgement of the positive aspects of XXY. Recommendations are made for how genetic counseling can enhance quality of life for individuals living with XXY.